2019
DOI: 10.1021/acsphotonics.9b00311
|View full text |Cite
|
Sign up to set email alerts
|

Scalable Large-Area p–i–n Light-Emitting Diodes Based on WS2 Monolayers Grown via MOCVD

Abstract: Transition metal dichalcogenides (TMDCs) represent a novel and sustainable material basis for ultrathin optoelectronic devices. Although various approaches toward light-emitting devices, e.g., based on exfoliated or chemical vapor deposited (CVD) TMDC monolayers, have been reported, they all suffer from limited scalability and reproducibility required for industrial fabrication. Here, we demonstrate a light-emitting device in a scalable approach by embedding metal−organic (MO-)­CVD WS2 monolayers into a vertic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
62
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 48 publications
2
62
0
Order By: Relevance
“…The luminescent layer is a three‐atom‐thick WS 2 monolayer with a room temperature photoluminescence (PL) emission around 2.04 eV. The fully coalesced TMDC monolayer has been grown by MOCVD on a 2” sapphire (0001) wafer and was transferred on top of the poly‐TPD layer using a polystyrene auxiliary layer in a semi‐dry approach [ 20 ] with modifications as described in the Supporting Information (Device Preparation). A layer of ZnO nanoparticles (NP) is spin‐coated on top of the active material and serves as electron injection/transport layer as well as hole blocking layer.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…The luminescent layer is a three‐atom‐thick WS 2 monolayer with a room temperature photoluminescence (PL) emission around 2.04 eV. The fully coalesced TMDC monolayer has been grown by MOCVD on a 2” sapphire (0001) wafer and was transferred on top of the poly‐TPD layer using a polystyrene auxiliary layer in a semi‐dry approach [ 20 ] with modifications as described in the Supporting Information (Device Preparation). A layer of ZnO nanoparticles (NP) is spin‐coated on top of the active material and serves as electron injection/transport layer as well as hole blocking layer.…”
Section: Figurementioning
confidence: 99%
“…The slight shift in peak wavelength—compared to the PL signal of the as‐grown WS 2 monolayer on sapphire (see Figure S3, Supporting Information)—might have different reasons. In previous works it has been shown that the PL peak shifts after the transfer of TMDC layers from the sapphire substrate into the device environment due to the change of the adjacent material and thus the dielectric environment [ 20,22 ] (see also Figure S3, Supporting Information). In addition, the emission energy can be influenced by built‐in fields of the p–n junction, by the external electric fields when applying a bias voltage and—in particular—by emerging Joule heating effects with increasing current density.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…[ 1,2 ] This makes them attractive for optoelectronic device applications. [ 3–5 ] TMDCs also show excellent spin–orbit coupling (control over polarization‐dependent band excitation), mobility, and strong exciton binding energies. [ 6–10 ] WS2 monolayers show higher luminescence quantum yield (≈6%) when compared with other TMDC monolayers (<1%).…”
Section: Figurementioning
confidence: 99%
“…Although the WSe 2 devices were bright, their emission is in the near‐infrared regime (750 nm peak emission). Recently, millimeter‐scale WS 2 devices operated in the visible wavelength regime were demonstrated using a vertical architecture with quantum dots and polymers as electron/hole injection layers, but a more efficient device is still demanded . In this regard, we report a centimeter‐scale, bright, visible light‐emitting device based on WS 2 monolayers synthesized via CVD using a simple capacitor structure.…”
Section: Introductionmentioning
confidence: 99%